PTH-099 A novel approach to the implementation of biosimilar infliximab ct-p13 for the treatment of ibd utilising therapeutic drug monitoring: the edinburgh experience. (17th June 2017) - Plevris, N; Manship, TA; Deekae, A; Jones, GR; Noble, CL; Satsangi, J; Shand, AG; Arnott, ID; Lees, CW
Abstract : Introduction: The introduction of biosimilar infliximab with CT-P13 offers substantial potential cost savings. Data on switching from Remicade to CT-P13 is only just emerging and was not available in early 2016. Therapeutic drug monitoring (TDM) is increasingly recognised as an effective means to optimise patient outcomes on anti-TNF therapy, but is not widely adopted in the UK. Following discussions with hospital management, we took the opportunity to implement TDM whilst switching patients established on Remicade to biosimilar CT-P13. Method: A switch pathway was agreed and implemented, with all data collected prospectively. Routine blood tests, disease activity scores (Partial Mayo/HBI), faecal calprotectin (FC) and serum for infliximab trough levels (ITL) and antibodies to infliximab (ATI) were obtained. Results were reviewed in a virtual biologics clinic and decision made on further management as per NICE DG-22 TDM algorithm. Clinical remission was defined as HBI <5 and Partial Mayo<2. Results: 169/170 patients currently receiving Remicade agreed to our switch process. 95/169 (56%) patients were switched to CT-P13 with no dose change whilst 15/169 (9%) switched with dose escalation and 8/169 (5%) with dose de-escalation. 27/169 (16%) patients stopped biologic therapy altogether due to a combination of immunogenicity (ITL<3 µg/ml; ATI>8 µg/ml), clinical and biochemical remission. 24/169 (14%) patients had immunogenicity with infliximab but were not in remission and therefore switched to an alternative biologic (ADA n=18; VDZ n=6). Remission rates of patients switched with no dose change were 97% pre-switch, compared to 91%, 95%, and 96% at week 6–8, week 12–16 and week 18–24 respectively. In the patients with CD (n=91) median HBI remained unchanged pre-switch and at week 6–8 (HBI 0, p=0.5), week 12–16 (HBI 0, p=0.5) and week 18–24 post-switch (HBI 0, p=0.4). There was no significant difference between ITL and incidence of ATI pre-switch and at week 18–24 (4.2 µg/ml vs 3.7 µg/ml, p=0.4; 30% vs 26%, p=0.5). 100% of patients who switched with dose de-escalation (n=8) remained in remission at week 18–24. Data on patients who switched with dose escalation or who stopped treatment are presently being analysed. No infusion reactions were reported. Health-economic evaluation of the switch process/TDM implementation has projected a cost-saving of approximately £7 00 000 in year 1. Conclusion: Our local experience further supports interchangeability between originator and biosimilar infliximab whilst also demonstrating the significant cost saving that can be achieved through the adoption of biosimilars and TDM. Disclosure of Interest: None Declared